In vitro evaluation of raft-forming and non-raft forming antacids marketed in India - Shinde, Ujwala A.; Sharma, Nisha S.; Petkar, Pradnya R.; Pawar, Kasturi K.; Patil, Anupama R.; Savla, Hemali; Ramaiya, Eesha (International Journal of Research in Medical Sciences, 2025)
Background: Raft properties of alginate‐antacids may vary based on their formulation. This study compared the physicochemical characteristics such as raft properties of Digeraft Plus® versus four other raft-forming (brands A to D) and acid neutralizing properties of raft-forming antacids versus two non-raft forming (brands E, F) antacids marketed in India. Methods: The study assessed acid neutralizing capacity (ANC), and acid neutralizing potential (ANP) of the raft and non-raft forming antacids and the effect of raft structure on neutralization profile, raft strength, and raft resilience of the raft-forming antacids. Sodium alginate content of the raft-forming antacids was measured by a validated high-performance liquid chromatography (HPLC) assay. Results: The raft-forming formulations were able to neutralize acid better than non-raft forming formulations. Total duration of acid neutralization of Digeraft Plus® was found to be 72±5.33 mins while for the other raft as well as non-raft forming antacid products, it was in the range of 40 to 60 mins. Additionally, it also had raft strength of around 20.5 gm which was significantly higher than other raft-forming brands (p<0.05) indicating enhanced raft integrity and retention. This performance correlates with its sodium alginate content, which was greater than 90%. Conclusions: Results indicate that minor differences in formulation can affect the raft properties, and consequently, its in-vivo clinical efficacy. The strength and resilience of the rafts varied between the different alginate-based antacids available in the Indian market. Compared to other antacids, Digeraft Plus® had greater ANP, raft strength, and raft resilience.